Comparing caring practices between two groups of pregnant women in the city of Sincelejo Comparación de las prácticas de cuidado en dos grupos de gestantes en la ciudad de Sincelejo - GARCÍA GARCÍA LUZ MARINA (Universidad Nacional de Colombia, 2008)
In order to compare the care practices that a group of pregnant women exercise in respect of themselves and their unborn child of a group of adolescent pregnant girls andanother of adult pregnant women who attended prenatal check ups in Sincelejo during the months of July and September of 2006, a descriptive, quantitative and transversal study was developed, with a sample of 97 adolescent pregnant girls between 15 and 19 years and of 153 adult pregnant women between 20 and 45 years of age, without associated pathologies, to whom an instrument on care practices was applied which is validated by the National University of Colombia in Bogotá. These practices were classified as good, average and poor in the two groups to establish the quantitative comparison thereof. The main results were: differences statistically significant in the dimensions of prenatal stimulation, hygiene and personal care, food and non-healthy substances; in these four dimensions the result of good practices was more favorable for the adult pregnant women; There was not a significant difference in the dimensions of exercise and rest and support systems. The majority of the adult pregnant women (81,7%) carried out household activities that caused them tiredness; 23,53% did not carry out any recreational activities; 25,77% of the adolescent pregnant girls and 41,18% of the adult pregnant women consumed diary foods. 19,59% of the adolescent pregnant women and 6,54% of the adult ones did not avoid alcohol consumption and 4,12% of the adolescent pregnant womenand 0,65%ofthe adultpregnantwomen had consumed psychoactive substances. Adolescents (68,04%) as well as adults (52,29%) would carry out practices of prenatal stimulation classified as regular. Only 31,37% of the adult pregnant women and 21,65% of the adolescent pregnant girls had adequate prenatal stimulation practices. Para comparar las prácticas de cuidado que realizan consigo mismas y con su hijo por nacer un grupo de gestantes adolescentes y otro grupo de gestantes adultas que asisten a control prenatal en Sincelejo, durante los meses de julio y septiembre de 2006, se desarrolló un estudio descriptivo, cuantitativo y transversal, con una muestra de 97 gestantes adolescentes entre 15 y 19 años y de 153 gestantes adultas entre 20 y 45 años, sin patologías asociadas, a quienes se les aplicó un instrumento sobre prácticas de cuidado, validado por la Universidad Nacional de Colombia, sede Bogotá. Estas prácticas se clasificaron en buenas, regulares y malas, en los dos grupos, para establecer la comparación cuantitativa de las mismas. Los principales resultados fueron: diferencias estadísticamente significativas en las dimensiones de estimulación prenatal, higiene y cuidados personales, alimentación y sustancias no beneficiosas; en estas cuatro dimensiones el resultado de buenas prácticas fue más favorable para las gestantes adultas; no se encontró diferencia significativa en las dimensiones de ejercicio y descanso, y sistemas de apoyo. La mayoría de las gestantes adultas (81,7%) realizaban actividades domésticas que les producían cansancio; 23,53% no desarrollaban actividades recreativas; 25,77% de las gestantes adolescentes y 41,18% de las gestantes adultas consumían lácteos. 19,59% de las gestantes adolescentes y 6,54% de las adultas no evitaban el consumo de licor y 4,12% de las gestantes adolescentesy0,65% de lasgestantes adultas habían consumido sustancias psicoactivas. Tanto adolescentes (68,04%) como adultas (52,29%) realizaban prácticas de estimulación prenatal catalogadas como regulares. Solo 31,37% de las gestantes adultas y 21,65% de las gestantes adolescentes tenían prácticas adecuadas de estimulación prenatal.